2021
DOI: 10.1108/mhrj-09-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service users’ lived experiences of recovery-oriented services: a scoping review

Abstract: Purpose Over the past 15 years, mental health organisations have taken steps to move towards providing services that are more recovery-oriented. This review was undertaken to explore what is known about service users’ experience of services that have introduced a recovery-oriented approach to service provision. There is limited research evaluating consumers’ lived experiences of recovery-orientated care; a scoping review was chosen to provide an overview of the available research in this area (Munn et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…In contrast, although some staff were seen as supportive, others found staff turnover to be problematic resulting in a lack of continuity, lack of access in times of need, and at times staff being slow to act. This finding supports the prior work of Lau and Hutchinson (2021), and Wood and Alsawy (2015), who found that relationships with mental health staff can either support or hinder recovery. This can be a particular challenge if consumers do not develop a trusting, collaborative relationship with professionals [10,11,16].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, although some staff were seen as supportive, others found staff turnover to be problematic resulting in a lack of continuity, lack of access in times of need, and at times staff being slow to act. This finding supports the prior work of Lau and Hutchinson (2021), and Wood and Alsawy (2015), who found that relationships with mental health staff can either support or hinder recovery. This can be a particular challenge if consumers do not develop a trusting, collaborative relationship with professionals [10,11,16].…”
Section: Discussionsupporting
confidence: 88%
“…This finding supports the prior work of Lau and Hutchinson (2021), and Wood and Alsawy (2015), who found that relationships with mental health staff can either support or hinder recovery. This can be a particular challenge if consumers do not develop a trusting, collaborative relationship with professionals [10,11,16].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous research on individuals with SMI and their caregivers has mainly focused on illness-related aspects. However, QoL studies provide a more comprehensive perspective, which aligns with the emphasis of the recovery model on the lived experiences of patients and their families (Lau & Hutchinson, 2021). This holistic approach integrates patient-centered factors, such as psychosocial and cultural, and emphasizes patient empowerment and autonomy.…”
Section: Introductionmentioning
confidence: 99%